A Method of Constructing Tooth Surface Without Backlash for Conical Line Gear - He Enyi; He Di; Wu Haihua; Du Yixian; Ye Xicong (Jixie chuandong)
Based on space curve meshing theory, a conical Line Gear (LG) mechanism without backlash is studied. A conical helix is selected as the driving contact line, and the driven contact line which conjugated with driving contact line is solved by the LG meshing theory. The concave-convex contact circular section, which is via contact point and perpendicular to the direction of angular velocity of the driving gear is established without backlash. The concave-convex tooth surfaces without backlash can be constructed by scanning the circular section along the center lines. Therefore, conjugate contact lines lie on the constructed tooth surfaces. The maximum number of teeth is discussed on the basis of the radius of section circle and the circumference of end cone. According to tooth surface equations, a 3-D model is established and kinematics simulation experiment is carried out. The result shows that the conical LG constructed by this method can realize the smooth transmission process with the designed transmission ratio. Based on meshing equation of LG, a method for constructing the tooth surface of novel conical LG is proposed, which provides a new solution for the orthogonal axis gear transmission.